Influence of sleep and physical exercise in migraine patients - Juliani , Maria Paula Bertoletti; Rocha, Amanda Brant; Zendrini, Giovana Ortiz; Salomão, Giovana Rodrigues; Lima , Giovanna Sguissardi de; Tirintan , Ana Laura; Silva, Aline Vitali da; Bello , Valéria Aparecida; Frederico, Regina Célia Poli (Headache Medicine, 2022)
Introduction The prevalence of headache and sleep disorders is quite high in the general population. Both are chronic pathologies considered factors of daily disability which often coexists in migraine patients. A cause-and-effect relationship between migraine attacks and sleepless nights has not been confirmed yet, but it is already recognized that they have in common neuropeptides and functional anatomy in their pathogenesis. Because of this high prevalence, there are several studies on treatment options and prophylactic measures for migraine. The regular practice of physical exercises is identified as an important prevention factor for migraine attacks. However, daily intense physical activities are identified as triggers for these attacks. Objectives To investigate the correlation between sleep time and frequency of physical activity with headache days per month, migraine disability, allodynia, hyperacusis, anxiety and depression. Methods Cross-sectional study composed of 466 individuals of both sexes diagnosed with migraine. Patient data such as age, sex, race, body mass index (BMI), waist circumference, presence of hypertension and diabetes were analyzed. It was obtained information about the type of migraine (episodic or chronic; with or without aura), age of symptoms onset, duration of illness, use of prophylactic medication and excessive use of analgesics, as well as hours of sleep per night and frequency of practice of physical activity. Patients answered questionnaires to evaluate disability (Migraine Disability Assessment - MIDAS) and the impact of migraine (HIT-6), as well as questionnaires for anxiety (STAI Y1 and STAI Y2), depression (Beck Depression Scale), allodynia (ASC-12) and hyperacusis. Spearman's correlation test was performed and a statistical difference was considered when p ≤ 0.05. (To see the complete abstract, please, check out the PDF).